The social sciences as another site of the Colombian conflict: An analysis based on the philosophy of Alasdair MacIntyre (2013)
The social scientific study of the Colombian armed conflict has become another setting of the conflict based on radical theoretical and philosophical disagreements. This is due to the inherent normative and ideological dimensions of the social sciences, w